Bio-Layer Interferometry Analysis of the Target Binding Activity of CRISPR-Cas Effector Complexes - Müller-Esparza, Hanna; Osorio-Valeriano, Manuel; Steube, Niklas; Thanbichler, Martin; Randau, Lennart (Frontiers in Molecular Biosciences, 2020)
CRISPR-Cas systems employ ribonucleoprotein complexes to identify nucleic acid targets with complementarity to bound CRISPR RNAs. Analyses of the high diversification of these effector complexes suggest that they can exhibit a wide spectrum of target requirements and binding affinities. Therefore, streamlined analysis techniques to study the interactions between nucleic acids and proteins are necessary to facilitate the characterization and comparison of CRISPR-Cas effector activities. Bio-layer Interferometry (BLI) is a technique that measures the interference pattern of white light that is reflected from a layer of biomolecules immobilized on the surface of a sensor tip (bio-layers) in real time and in solution. As streptavidin-coated sensors and biotinylated oligonucleotides are commercially available, this method enables straightforward measurements of the interaction of CRISPR-Cas complexes with different targets in a qualitative and quantitative fashion. Here, we present a general method to carry out binding assays with the Type I-Fv complex from Shewanella putrefaciens and the Type I-F complex from Shewanella baltica as model effectors. We report target specificities, dissociation constants and interactions with the Anti-CRISPR protein Acr7 to highlight possible applications of this technique.